Development of early embrionic stage of laboratory mouse - Bačić, Goran; Slavica, Alen; Mihelić, Damir Tomić, Davorka; Bratulić, Mirna Hincak, Zdravka (1995)
Early development of laboratory mouse in first embryonic stage was studied.
ENG